A COMPARATIVE ANALYSIS OF EMPLOYEE ENGAGEMENT AND EMPLOYEE PERFORMANCE: A STUDY OF PT TRAKINDO UTAMA EMPLOYEES - Nunung Nurastuti Utami (Bajang Institute, 2025)
This study aims to examine and analyze differences in employee performance and employee engagement between male and female employees at PT Trakindo Utama Samarinda. Using an independent sample t-test analysis, the results of the t-test were 0.043 (sig: 0.966) and -0.197 (sig: 0.44), respectively. This indicates that there is no difference in employee performance and employee engagement between male and female employees at PT Trakindo Utama Samarinda. It can be concluded that both male and female employees have similar levels of employee performance and employee engagement. The analysis suggests that there is no need to differentiate policies and treatment related to human resource development, either in methods or treatment, between male and female employees, and that they are given equal opportunities.